Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s40104-019-0371-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro protective effect of arginine against intestinal inflammatory response induced by Clostridium perfringens in broiler chickens

Abstract: Background Necrotic enteritis is a widespread disease in poultry caused by Clostridium perfringens. We previously reported that dietary arginine supplementation protected the intestinal mucosa of broiler chickens with necrotic enteritis, but the related protective mechanisms remain unclear. The in vivo trial was designed as a 2 × 2 factorial arrangement to evaluated the effects of arginine supplementation on inflammatory responses, arginine tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
6
34
0
Order By: Relevance
“…The main transporters for Arg influx are cationic amino acid transporters that influence the intracellular concentration of Arg (Lu et al., 2013). Additionally, numerical decrease in jejunal CAT‐1 is consistent with another study (Zhang et al., 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The main transporters for Arg influx are cationic amino acid transporters that influence the intracellular concentration of Arg (Lu et al., 2013). Additionally, numerical decrease in jejunal CAT‐1 is consistent with another study (Zhang et al., 2019).…”
Section: Discussionsupporting
confidence: 91%
“…However, supplementation of C. butyricum lowered the upregulation of TGFB1, IL-10, IL-6, and TNF-α observed in NE infection. Our ndings support the increase in cytokine secretion after the addition of probiotics or food additives that can reduce in ammation after pathogens infection in broilers and pigs [6,7,12,43]. This result shows that an increase of immune factors caused by NE owing to C. perfringens stimulates the in ammatory immune response in the intestine.…”
Section: Discussionsupporting
confidence: 80%
“…The data on the activity of bacterial extracellular enzymes ( Table 5 ) indicated that Arg was more effective in promoting the extracellular activity of bacterial enzymes than Lys. According to Zhang et al [ 46 ], an increased inclusion rate of Arg (3 g/kg higher than that recommended for Arbor Acres broiler chickens by the NRC) counteracted circulating Arg deficiency in C. perfringens -challenged chickens, which may indicate that in our study, larger amounts of this AA were available for stimulating the glycolytic activity of bacteria in turkeys fed high-Arg diets. The increased glycolytic activity of gut microbiota may be indicative of their better adaptation for energy uptake from the available substrates.…”
Section: Resultsmentioning
confidence: 50%